2018
DOI: 10.3390/electronics7100227
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Analysis in Sub-0.1 μm for Partial Isolation Field-Effect Transistors

Abstract: In this paper, we extensively analyzed the drain-induced barrier lowering (DIBL) and leakage current characteristics of the proposed partial isolation field-effect transistor (PiFET) structure. We then compared the PiFET with the conventional planar metal-oxide semiconductor field-effect transistor (MOSFET) and silicon on insulator (SOI) structures, even though they have the same doping profile. Two major features of the PiFET are potential condensation and potential modulation by a buried insulator. The poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…In this paper, we proposed a new device with a partial isolation region under the storage node of conventional S-FinFET. This structure can be fabricated by using an isotropic dry etching technique for the buried insulator under the cell transistor [7,8]. We analyzed electrical characteristics of this proposed device and compared them with those of conventional S-FinFETs of the same size.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this paper, we proposed a new device with a partial isolation region under the storage node of conventional S-FinFET. This structure can be fabricated by using an isotropic dry etching technique for the buried insulator under the cell transistor [7,8]. We analyzed electrical characteristics of this proposed device and compared them with those of conventional S-FinFETs of the same size.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed FinFET exhibited four times lower I off than modified S-FinFET, called RFinFET, with more improved drain-induced barrier lowering (DIBL) characteristics, while minimizing I on reduction compared to RFinFET. Our results also confirmed that the proposed device showed improved drain-induced barrier lowering (DIBL) and I off characteristics as gate channel length decreased.Keywords: gate-induced drain leakage (GIDL); drain-induced barrier lowering (DIBL); recessed channel array transistor (RCAT); on-current (I on ); off-current (I off ); subthreshold slope (SS); threshold voltage (V TH ); saddle FinFET (S-FinFET); potential drop width (PDW); shallow trench isolation (STI); technique for the buried insulator under the cell transistor [7,8]. We analyzed electrical characteristics of this proposed device and compared them with those of conventional S-FinFETs of the same size.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This issue collected two approaches to achieve a steep SS: (1) using the insulator-metal phase transition of VO 2 to achieve a decent SS of 42 mV/dec [6]; (2) using an L-shaped tunneling FET to improve the SS [7]. In addition, the drain-induced barrier lowering (DIBL) effect and leakage of a partial isolation FET for sub-0.1 µm have been studied [8].…”
Section: The Current Research Trendsmentioning
confidence: 99%
“…To address this issue, Pi-FinFETs (Pi-SFinFET, Pi-RFinFET) that have a partial isolation region under the storage node of S-FinFETs (SFinFET, RFinFET) have been proposed [12][13][14]. However, in Pi-FinFETs fabricated using an isotropic dry etching technique where the insulator is buried under the cell transistor [15,16], the buried insulator can cause an interface trap between itself and the drain region [17]. Consequently, this can have an adverse effect on leakage current.…”
Section: Introductionmentioning
confidence: 99%